Determinação de chumbo por análise voltamétrica de pulso diferencial por redissolução anódica em regiões de falhas geológicas com emissão de radônio e filhos de radônio no município de Presidente Prudente - Silva Junior, Marcos Roberto Moreira da [UNESP] (2015)
The major objective of this work was the quantification of lead (Pb) in soil samples from different horizons, in specific areas of the city of Presidente Prudente / SP. The collection points were established according to the data on the emanation of Rn (detector CR-39) and mapping of geological faulting guidelines. Soil sample on the FCT-UNESP represented the areas of geological fault, and collected two samples in a rural area in Montalvão District, free of geological fault, which were deployed in trenches in the region of geological failure for further analysis. The USEPA 350 method was effective for the preparation of soil samples, providing the quantification of Pb using voltammetric analysis. The optimized experimental parameters: volume of the sample and pre-concentration time, were 2 ml and 30 s, respectively, as demonstrated a greater increase in current magnitude and were sufficient to perform the analyzes. We used the technique anodic stripping voltammetric with mercury electrode, which was satisfactory and proved to have a low detection limit. The metals Zn, Cd and Cu were not presented as possible interferences for determining the analyte interest. According to the quantitative analysis of Pb, the metal concentrations were higher in areas of the Campus of FCT - UNESP, and too lower in the samples of Montalvão District. Soil profiles incubated in the trenches, after 95 days of incubation, suffered a sharp increase in lead concentration demonstrating the significant influence that the geological fault region has in relation to the increase in Pb concentrations in soils, indicating that the origin of lead can be directly connected to emanation of radon gas, which comes from the lower base of the soil profile, more specifically of the bedrock anomalies. The data obtained from the grain size analysis revealed that the soils collected in the alleged fault region are the textural classes Sand...